Assessment of mangrove structures and biomass on islands along the Java Sea: a case study on Bawean Islands and Karimunjawa Islands - Asadi, Muhammad Arif; Al-kareem, Alvu Sya’ban; Aprilianto, Riqki Yoga; Sartimbul, Aida; Yamindago, Ade; Saputra, Dhira Khurniawan; Riyadi, Achmad (Frontiers in Ecology and Evolution, 2024)
Mangroves on the islands along the Java Sea play a crucial role in supporting biodiversity, protecting coastlines, and sequestering carbon. However, there is a lack of information on mangrove structure and biomass in the area. This study aimed to assess the mangrove structures and biomass on Desa Daun, located on the Bawean Islands, and Kemujan Island, located on the Karimunjawa Islands, respectively. The study utilized a combination of line transect and quadrant plot methods with a size plot of 10x10 m. We established 7 line transects and 28 quadrant plots in the mangrove forest of Desa Daun and similarly set up 7 line transects and 21 quadrant plots on Kemujan Island. Within each quadrant, the mangrove species were identified, and their diameters at breast height (DBH) were recorded. To assess the relative significance of each species, the importance value index (IVI) was calculated, and allometric equations were applied to estimate biomass and carbon storage in the trees. PlanetScope imagery was also used to quantify the carbon stock of mangroves on those islands. In Desa Daun, 13 mangrove species were identified, while 12 species were recorded on Kemujan Island. The species Nypa fruticans and Excoecaria agallocha exhibited the highest IVI in Desa Daun and Kemujan Island, respectively. Notably, Rhizophora apiculata demonstrated the greatest biomass in both locations, with measurements of 43.08 Mg B/ha in Desa Daun and 102.22 Mg B/ha in Kemujan Island. Overall, mangrove stands on Desa Daun stored biomass of 113.60 Mg B/ha and carbon of 50.98 Mg C/ha, whereas mangrove stands on Kemujan Island stored biomass of 295.04 Mg B/ha and carbon of 131.95 Mg C/ha. Mangrove stands of the whole Bawean Islands sequestered 22,941 Mg C, while Karimunjawa Islands hold much higher C stocks, 79,451 Mg C. Despite being smaller in size, the Karimunjawa Islands have more extensive mangrove coverage compared to the Bawean Islands due to their geomorphological characteristics, which in turn influence their mangrove structures and carbon stocks. However, the loss of mangroves in the Karimunjawa Islands due to aquaculture expansions could increase carbon loss in the islands.